Technology-Based Learning Innovations in Increasing Student Engagement - Leni Khoirus Safitri (PT. AVID MEDIA INDONESIA, 2025)
This study aims to analyze the contribution of technology-based learning innovations to increasing student engagement through a qualitative approach and literature review. The integration of technology into learning provides opportunities for teachers to present materials that are more interactive, adaptive, and relevant to students' needs. Various digital media such as simulations, learning applications, and collaborative platforms have been shown to strengthen student attention, motivation, and participation. The study results indicate that technology-based learning can enrich the learning experience through personalization, increased interactivity, and strengthened data-based evaluation. Digital collaboration also plays a role in developing social skills and critical thinking skills. However, challenges such as limited teacher competency, infrastructure readiness, and differences in access among students remain major obstacles. This literature review emphasizes the importance of strategies to strengthen teacher capacity, select appropriate technology, and conduct continuous evaluation to ensure optimal technology utilization. These findings confirm that technological innovation has significant potential to increase student engagement if its implementation is designed systematically and sustainably. This research is expected to serve as a reference for educators and educational institutions in developing learning strategies.